Pengaruh Keterampilan Interpersonal, Kecerdasan Emosional dan Motivasi Ekstrinsik Terhadap Kinerja Karyawan Bank Central Asia Cabang Medan - Susanti, Sintia (Graha Mitra Edukasi, 2023)
Whether or not performance is successful is influenced by several factors, namely motivation, discipline, and interpersonal skills both individually and in groups. Based on this description, the authors are interested in conducting research with the title: